TO EVALUATE PLASMA LIPID PROFILE PARAMETERS AND THEIR INTERNAL RATIOS IN CLINICALLY SUBGROUPED PSORIASIS PATIENTS: A COMPARATIVE STUDY - Dr. Ananya Choudhary , Dr Rajendra Devanda , Dr Khushboo Gupta , Dr U.S Agarwal (Journal of Population Therapeutics and Clinical Pharmacology, 2025)
Background: Psoriasis is a chronic inflammatory skin disorder associated with metabolic abnormalities, including dyslipidemia. Alterations in plasma lipid profiles and their internal ratios may contribute to increased cardiovascular risk in psoriasis patients.Objective: To evaluate plasma lipid profile parameters and their internal ratios in clinically sub-grouped psoriasis patients compared to healthy controls.